Conceptual progress in understanding fear of crime in railway stations - Uzzell,David (2007)
Previous research demonstrates there are discrepancies between actual crime and perceived beliefs about crime. The likelihood of threatening incidents and the potential impact of a given incidents are the focus of the present study of how psychological and environmental cues influence people's fear of crime in railway stations. Having established the salience of individuals construct evaluations of the likelihood and impact of being the victim of crime based upon travellers experiences and observations, the analysis demonstrated that conceptualisations of impact and likelihood are multifaceted, i.e. different types of threats influence evaluations including psychological threats as a result of the actions of others, physical threats initiated by others and threats posed by the railway station environment itself. The implications of these findings are discussed for the design and management of railway station environments.